Associations of active commuting to school in childhood and physical activity in adulthood - Kaseva Kaisa; Lounassalo Irinja; Yang Xiaolin; Kukko Tuomas; Hakonen Harto; Kulmala Janne; Pahkala Katja; Rovio Suvi; Hirvensalo Mirja; Raitakari Olli; Tammelin Tuija H; Salin Kasper (Nature Publishing Group, 2025)
This study examined whether active commuting to school in childhood and adolescence predicted active commuting to work and overall physical activity (PA) in adulthood. Participants from the Young Finns Study (N = 2436) were aged 9-18 years in 1980 and followed up until 2018/2020. Their commuting modes to school were assessed with a self-reported questionnaire in 1980. Adulthood PA was assessed through self-reports regarding commuting modes to work (2001-2018), leisure-time physical activity (LTPA) (2001-2018), and objectively measured daily steps (2007-2018/2020). Associations between childhood commuting and adulthood PA were evaluated using regression analyses and multilevel models. Demographic, socioeconomic and environmental covariates were adjusted for in the analyses. Active commuting to school in childhood contributed favourably to LTPA in 2001 (B = .38, p < .001), in 2007 (B = .35, p < .001), and in 2018 (B = .28, p < .01). Active commuting in childhood was associated with higher number of daily aerobic steps (B = 299.00, p = .03) and daily aerobic steps during weekdays in 2011 (B = 312.15, p = .03). In 2018, active commuting associated favourably with daily aerobic steps (B = 370.42, p < .01), daily aerobic steps during weekdays (B = 347.65, p = .01), daily steps during weekends (B = 628.49, p = .02), and daily aerobic steps during weekends (B = 402.69, p = .03). Covariate adjustments attenuated the associations excluding the one between active commuting and LTPA in 2007 (B = .36, p = .01) and daily steps during weekends in 2018 (B = 782.25, p = .04). Active commuting to school in childhood might be one of the PA modes that contribute to PA in adulthood and is therefore encouraged to be promoted from an early age.